Comprehensive Earthquake Analysis And Visualization Using Tableau Tool - Chandran, Abhishek J; Biju, Jovita; Poulose, Alwin (2024 5th International Conference on Innovative Trends in Information Technology (ICITIIT), 2024)
This paper presents an extensive seismic data analysis using Tableau as a gateway. Earthquakes bring on landslides, tsunamis, and other deadly natural disasters. Therefore, for a more successful analysis, it is essential to comprehend the components associated with earthquakes. We start our data analysis by examining the trends or periodicity of earthquake occurrence on a monthly and annual basis. This aids in determining the precise time at which earthquakes occur. Next, we discuss the various categories that exist for earthquakes. Seismic occurrences are classified into classes according to their magnitude and range, with each class displaying a different degree of destruction. Understanding the frequency at which these various classes occur is essential to having a thorough understanding of seismic patterns. Subsequently, we show the relationship between earthquake frequency, depth, and magnitude. Since these two variables are essential to the research on the subject, we next look for any correlation between magnitude and depth. After that, we examine a worldwide map to show how earthquakes are distributed geographically, offering an in-depth understanding of areas with a high frequency of seismic activity. Developing techniques for efficient risk mitigation requires this exploration. Tableau's integration into this study ensures dynamic and informative visualizations, allowing users to explore the data in real time and customize views to meet their interests or questions. This comprehensive analysis is presented in a way that advances the global understanding of earthquakes and makes the paper an invaluable resource for researchers, policymakers, and the general public.